(3CSO GdZGHg aj eYQaI GdUMGHgs - (3Ydj Hf eMeO Hf YHO GdcQje Hf YHO GdhGMO GdTjHGfj GdLRQj, CHh GdMSf YR GdOjf GHf GdCKjQ,J (B630 (3g` s ((3YHOGdZfi Hf YHOGdeDef Hf EHQGgje Hf HOQ GHf Hi GdYScQ GdHjGJi s)
(3ChdgG (B:s
(3HYO GdHSedI MQa Gdeje HGH Gdeje hGdCda eGLhQ GdNUHi GgOGg GdebhbS UGMH GdEScfOQjI s
(3BNQgG (B:s
(3aQeGgG NGdO HMLQ afaM GdOe Ydi hLgg aSHgG aSeY GdfHi SHg CjGgG abGd dg ahGdPi faSi HjOg aUdi YdjgG hOafJ aQZ ef fSNI s
(3GdLRA GdKGdK ef GdfSNI faSgGs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B331 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B228s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B15 s
Keywords: (3GdJGQjNs